Pengawasan Pemilihan Umum di Era Post-Truth: Problem, Tantangan, dan Strategi - Ayon Diniyanto; Wahyudi Sutrisno (Badan Pengawas Pemilihan Umum, 2022)
The 2024 election related with a post-truth era. This makes the potential for problems and challenges that must be faced and resolved. This study formulates problems (1) what are problems and challenges of supervising General Election in the post-truth era? and (2) what is the general election monitoring strategy in the post-truth era? The purpose of this research is to find the problems and challenges of general election supervision in the post-truth era; and (2) formulating a strategy for monitoring the General Elections in the post-truth era. The research method used in this study is a qualitative approach and the type of juridical normative research. The results of the study show that there are problems that will or have occurred in the post-truth election, such as (1) low digital literacy; (2) limited human resources related to election supervision in the digital realm; and (3) the lack of regulation on election law enforcement in the post-truth era. Potential challenges exist for example (1) large internet users in Indonesia; (2) the potential for intervention by other countries through digital; and (3) the effect of the division of society as a result of the election. The strategy that must be carried out is by using two approaches, namely prevention and action.